2018
DOI: 10.1002/da.22817
|View full text |Cite
|
Sign up to set email alerts
|

Screening and follow-up for depression among Arab Americans

Abstract: Our study adds to the discourse on depression care among Arab Americans by highlighting the existing disparities related to adequate screening and appropriate management of depression. Future studies should include information about the influences of acculturation, culture, stigma, family, and religion on depression care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The difference in the prevalence of depression is caused by regional differences. In high-income countries, such as the proportion of elderly depression is 6.6% (the United States) [ 10 ] and 3.7% (Singapore) [ 11 ]. In contrast, the incidence of depression in the elderly in low-and middle-income countries is higher [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the prevalence of depression is caused by regional differences. In high-income countries, such as the proportion of elderly depression is 6.6% (the United States) [ 10 ] and 3.7% (Singapore) [ 11 ]. In contrast, the incidence of depression in the elderly in low-and middle-income countries is higher [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increase in mental health challenges that Muslims face these days, there is general hesitation in seeking professional mental health care. [112] Arab-Americans are less likely to be screened for depression, and are similarly less likely to follow up with a behavioral health specialist, but they are more likely to follow up with a primary care clinician [113] . Muslim immigrants specifically may face a different set of issues, including a lack of understanding of Western healthcare systems, misunderstanding of terms used to describe mental health symptoms and diagnoses, and certain beliefs or perceptions of healthcare treatment [114] .…”
Section: Resultsmentioning
confidence: 99%
“…With most older adults having other comorbid chronic conditions that need to be addressed during primary care visits (38), there may be limited opportunities for early detection and screening for ADRD while addressing other health concerns (39). Existing literature has identi ed a wide range (5.5%-60%) of prevalence estimates for depressive symptoms among MENA individuals using community-based convenience samples (40)(41)(42), electronic health record data (43,44), and nationally representative samples (10,45). For example, using linked NHIS and MEPS data, Kindratt and colleagues reported that 38.2% of MENA adults ages 65 and older had depressive symptoms (10).…”
Section: Discussionmentioning
confidence: 99%